Constitutional Ethics Rooted in Customary Values: Comparative Analysis between Indonesia and Russia - Amin, Fakhry; Begishev, Ildar Rustamovich (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Constitutional ethics reflect the moral dimension that guides the administration of the state based on the cultural and historical values of the nation. Every country in the global context has a root value that shapes the character of its constitution. Indonesia and Russia are interesting examples because they both place local ethics, culture, and traditions as the basis for constitutional legitimacy.Purposes of the Research: This research aims to analyze and compare how customary and cultural values affect the formation and implementation of constitutional ethics in Indonesia and Russia. Through this study, it is hoped that a deeper understanding of the relationship between culture, ethics, and the constitution as the main pillars of morality in modern governance can be found.Methods of the Research: The research method used is qualitative and comparative with normative and socio-cultural approaches. Data was obtained through literature studies of constitutional documents, legal texts, and the results of previous research. The analysis was carried out in a descriptive-comparative manner to explore the similarities and differences between the two legal systems in internalizing customary-based ethical values into constitutional principles and state practices.Results of the Research: The findings show that both Indonesia and Russia have strong constitutional ethics rooted in the traditions of their people. Indonesia emphasizes social harmony, mutual cooperation, and social justice based on Pancasila, while Russia emphasizes the values of loyalty, national solidarity, and spirituality. Although they differ in their source of value, they show that the constitution is not just a legal document, but a reflection of the nation's moral and cultural identity that strengthens the state's legitimacy and social integrity.